THE EFFECTS OF BRINE COMPONENTS ON WETTABILITY ALTERATION OF CARBONATES DURING SURF ACT ANT FLOODING - HOSSEINI, SEYEDNOOROLDIN· (2017)
Carbonate reservoirs comprise more than 60% of world's reservoirs. More than 65% of the oil of these reservoirs cannot be produced by traditional production methods. Waterflooding has been widely used to produce oil from carbonate reservoirs but the recovery factor of this method is very low due to the low sweep efficiency and early water breakthrough. To tackle these problems surfactants can be used. Surfactants are chemicals which are added to injection water to reduce the surface tension between oil and water and to change the wettability of the rock surface from oil wet to water wet which results in higher oil recovery factor. This study investigates the effect of various salts (NaCl, CaCh, Na2S04 and MgCh) in the formation water on wettability alteration oflimestone rocks by a surfactant flooding process. To study the wettability, the method of measuring the contact angle between the drop and the rock surface was employed. The Design ofExperiment software (DOE) was used to get a thorough and systematic investigation and to design and analyze the experiments.